EFFECTS OF FEEDING DIET CONTAINING RAW OR PARBOILED RICE OFFAL ON RUMEN METABOLITE OF BUNAJI BULLS (FUDMA JOURNAL OF SCIENCES, 2023)
Twenty Bunaji bulls aged 2-3 years with an average weight of 230kg were assigned to five dietary treatments with four bulls per treatment in a 2x2 factorial configuration with common control to determine the effect of feeding diet containing varying inclusion of raw or parboiled rice offal on bull rumen metabolites which lasted for 90 days. Rumen fluid was collected at 0, 2, 4, and 6 hr intervals to assess rumen pH, rumen ammonia nitrogen (RAN), and rumen total volatile fatty acid (TVFA). Digitaria smutsii concentrate and basal diet were provided at 2% bogy weight. Crude Protein content of the experimental diets ranged from 19.69- 20.44%, while Metabolizable Energy content ranged from 10.86-11.16MJ/kg DM. Rice offal type had no effect on rumen parameters (P>0.05). Rumen pH six hours after feeding at 0% (6.63) and 30% (6.76) inclusion levels was similar (P>0.05), but differed considerably (P0.05). Bulls fed 30%PRO had the highest value (22.41g/100g), while bulls fed 20% PRO had the lowest value (14.80g/100g). This study indicated that RRO or PRO can be utilized to replace up to 30% of maize offal as a source of energy in the diet of Bunaji bulls with no negative effects on the bulls' rumen metabolite.
Keywords: Bunaji bull; Parboiled rice offal; Raw rice offal; Rumen metabolite